Sociological analysis of the corporate social responsibility assessments by the universities’ representatives (The Journal of Psychology and Sociology, 2017)
The article analyzes the data from sociology survey conducted at the universities in Kazakhstan. The trend of increasing social responsibility of higher education institutions and enhance their social functions today is very urgent for the international community. Over the last decade, this topic is accompanied by active international discussions, which are usually linked to the difference in terms of the functioning of universities in different countries. In addition, most researchers noted the complexity of the selection is the social aspects of diversity in university activities. In Kazakhstan’s system of higher education is also introduced elements of corporate social responsibility. Social functions are carried out by universities in many respects by offering the general public the possibility of education, training and retraining of specialists, creation of new jobs. An important role in this process plays the involvement of universities to the social, economic and cultural life of the city and the region. The study of opinions and value orientations among university respondents regarding the issues of social responsibility reveals that the modern state of this practice in Kazakhstan. Content analysis of the strategic development programs of universities has shown widespread lack of the concepts of “corporate social responsibility”, “social function”, “contribution to local community development” in the texts of the strategic programs. Only in two universities strategy developments mentioned the category of “socially-oriented activity,” by which is understood mainly educational and social work with students. Accordingly, at this stage of the investigation it was suggested that the Kazakh universities in relation to social responsibility are not developed a special strategy. The social function, is generally understood as a derivative from other types of universities. The conducted survey and analysis of university development programs reveal that social responsibility today is not as prioritized as, for instance, breakthrough scientific research development programs. However, although social work is not being delivered on articulate/well-defined objectives of implementing social functions, it is widely implemented by the universities in Kazakhstan. In most cases, it is derived from implementation of other functions, such as education, training, and research. Also, the author analyze facilitating and impeding reasons and factors of universities’ socially oriented activities.
Keywords: university; region; social responsibility; social function; social partnership.